Classroom influence—Do students with high autistic traits benefit from their classmates’ social skills? - Nenniger, Gina (Frontiers in Education, 2022)
Children and adolescents with intellectual disability (ID) and high levels of autistic traits often attend special needs classrooms where they spend a lot of time with other students who demonstrate diverse impairments and competencies. Research in typical development shows that classmates and the classroom composition in terms of specific classmate competencies can have a strong impact on individual social development. In this context, classmates’ social skills are of particular interest, as they are associated with successful social interaction and the ability to establish and maintain social relationships. Based on these associations, the present study investigated whether the levels of autistic traits and social skills in children and adolescents with ID and high levels of autistic traits are influenced by their classmates’ levels of social skills. A longitudinal design was used, with the first measurement point at the beginning of the school year and the second at the end of the school year. School staff members provided information on 330 students with ID and high levels of autistic traits (20.6% girls; mean age 10.17 years, SD = 3.74) who were schooled in 142 classrooms across 16 Swiss special needs schools. Results showed that students’ individual levels of autistic traits and social skills at T2 were not predicted by the classroom level of social skills at T1 when controlling for individual levels of autistic traits, individual levels of social skills, gender, age, and general levels of functioning at T1. Considering the present findings, perspectives for further research and support of children and adolescents with ID and high levels of autistic traits within the classroom context are discussed.